ANALISIS TEKS: KOHESI DAN KOHERENSI, UNSUR-UNSUR GRAMATIKAL SERTA IMPLIKATUR OPINI DI SURAT KABAR KOMPAS EDISI RABU, 27 MEI 2026 - Doni Uji Windiatmoko (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2026)
The purpose of this study is to determine the cohesion and coherence, grammatical elements, and implicature in the opinion of "Idul Adha" in Kompas Newspaper edition Wednesday, May 27, 2026. The form of this research is qualitative research. The object of this research is cohesion and coherence, grammatical elements, and implicature in the opinion of "Idul Adha Politik". The data in this study is in the form of text in the "opinion" rubric. The method in this study uses a qualitative descriptive textual research method. The results of this study are from the existing data found 3 data analysis of cohesion and coherence contained in paragraphs 1 and 2, paragraph 3, and paragraph 4. Then found data analysis of grammatical elements. (1) The references that appear are paragraph 1, paragraph 2, paragraph 4, paragraph 7, paragraph 8, paragraph 9, paragraph 10, paragraph 12, paragraph 13, and paragraph 14. (2) The substitutions in paragraph 1 contain 4 words, paragraph 2 contains 3 words, paragraph 3 contains 3 words, paragraph 4 contains 2 words, paragraph 5 contains 3 words, paragraph 6 contains 3 words, paragraph 7 contains 3 words, paragraph 8 contains 3 words, paragraph 9 contains 7 words, paragraph 10 contains 2 words, paragraph 11 contains 2 words, paragraph 12 contains 2 words, paragraph 13 contains 1 word, paragraph 14 contains 4 words, and paragraph 15 contains 1 word. (3) The conjunctions that appear are in paragraph 2, paragraph 3, paragraph 4, paragraph 6, paragraph 7, paragraph 8, paragraph 9, paragraph 10, paragraph 11, paragraph 12, and paragraph 15. Here, data on ellipsis and parallelism is not found. And there is an implicature. Keywords: Cohesion and Coherence, Grammatical Elements, Implicature